2010
DOI: 10.1111/j.1468-3083.2009.03563.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the best outcome measures for assessing quality of life in plaque type psoriasis? A systematic review of the literature

Abstract: On the basis of this systematic review, we can conclude that the DLQI is easy to use in clinical practice because of its brevity and simplicity. SF36 is widely used in clinical trials. Skindex 29 and Skindex 17, although rarely used, are interesting because of their cross-cultural validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 16 publications
3
111
0
4
Order By: Relevance
“…The DLQI is a reliable and valid instrument [7,10,11] . However, it has fallen short in some other aspects of psychometric performance in particular unidimensionality and item bias [12][13][14][15] . Hongbo et al [16] have demonstrated a banding system to aid the interpretation of DLQI scores, but a frequent question still arises: what does a specific improvement, such as 2, 5 or 6 points, in a DLQI score mean to a patient (and to the physician)?…”
Section: Introductionmentioning
confidence: 99%
“…The DLQI is a reliable and valid instrument [7,10,11] . However, it has fallen short in some other aspects of psychometric performance in particular unidimensionality and item bias [12][13][14][15] . Hongbo et al [16] have demonstrated a banding system to aid the interpretation of DLQI scores, but a frequent question still arises: what does a specific improvement, such as 2, 5 or 6 points, in a DLQI score mean to a patient (and to the physician)?…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the clinical measure psoriasis area and severity index (PASI) and the dermatology-specific HRQOL measure dermatology quality of life index (DLQI) are widely used and valid measures in psoriasis [11,12,13,14,15,16,17]; the generic preference-based EQ-5D questionnaire is a good complement [18], essential in cost-effectiveness analyses [19]. …”
Section: Introductionmentioning
confidence: 99%
“…A survey of National Psoriasis Foundation members also found a high rate of dissatisfaction with treatment among psoriasis patients (52.3%) and PsA patients (45.5%), and cited adverse effects and efficacy as the main reasons for discontinuation of biologic therapy. Patient-reported outcomes, such as health-related quality of life measures, have been increasingly studied in large randomized trials of psoriasis therapies since conventional clinical measures do not fully inform the effects of disease and treatment on patients [32,33]. Commonly used health-related quality of life measures focus on the impact of the disease on physical, psychological, and social functioning, but not the impact of the treatment experience on these factors.…”
Section: Discussionmentioning
confidence: 99%